MANAJEMEN KONFLIK KEAGAMAAN: KASUS ALIRAN ISLAM TAUHID DI KABUPATEN PANDEGLANG: MANAGEMENT OF RELIGIOUS CONFLICT: THE CASE OF ISLAM TAUHID IN PANDEGLANG, BANTEN - Novi Dwi Nugroho (Penamas, 2014)
This article provides the results of a research on an Islamic sect called Islam Tauhid in Pandeglang District, Banten Province, and the way through which the local government managed religious conflict involving this group. The methods used for the study comprised interviews, document study, and focus group discussion. The author found that one of the reasons why the local branch of MUI (Majelis Ulama Indonesia) considered Islam Tauhid as a deviant sect was that Juneidi, the founder of the sect, taught that instead of practicing prayer (shalat), Muslims only need to remember God. Besides, he also taught that Friday prayer was not an obligation for Muslim men. And in order to attract his young Muslim audience, he delivered his sermons on Islam through playing chess and dominoes. Mass violence occurred against this sect resulting in the burning of Junaidi’s house, even though Junaidi and his assistant could be safely evacuated to the police office. The author argues that fatalities could be prevented because of quick responses from, and good coordination among,the elements of local government, such as the district government, security apparatus, Bakorpakem, and the district- level Ministry of Religious Affairs, as well as non-government institutions, such as MUI and FKUB (Forum Kerukunan Umat Beragama). Key Words: Islam Tauhid, Islamic sect, religious conflict management, Pandeglang. Tulisan ini menyajikan hasil penelitian tentang paham yang diajarkan oleh aliran Islam Tauhid, sehingga dianggap sesat, dan manajemen konflik keagamaan yang dilakukan oleh Pemerintah Daerah Kabupaten Pandeglang. Penelitian ini menggunakan metode wawancara, studi dokumen, dan focus group discussion. Peneliti menemukan, bahwa salah satu alasan mengapa cabang lokal dari MUI (Majelis Ulama Indonesia) menganggap Islam Tauhid sebagai aliran sesat adalah, bahwa Junaidi, pendiri sekte, mengajarkan umat Islam hanya perlu mengingat Tuhan daripada salat. Selain itu, dia juga mengajarkan, bahwa salat Jum’at itu bukan kewajiban bagi laki-laki Muslim. Dalam rangka untuk menarik kalangan muda Muslim, dia menyampaikan khutbah tentang Islam melalui bermain catur dan domino. Hal ini memicu kekerasan massa terjadi terhadap sekte ini, yang mengakibatkan pembakaran rumah Junaidi, meskipun Junaidi dan asistennya bisa selamat diungsikan ke kantor polisi. Peneliti berpendapat, bahwa kematian dapat dicegah karena respon cepat dari, dan koordinasi yang baik di antara, unsur pemerintah daerah, seperti pemerintah kabupaten, aparat keamanan, Bakorpakem, dan Departemen Agama tingkat kabupaten, serta lembaga non pemerintah, seperti MUI dan FKUB (Forum Kerukunan Umat Beragama). Kata Kunci: Manajemen konflik, aliran keagamaan, aliran Islam Tauhid, Pandeglang.